2009
DOI: 10.1136/sti.2009.037820
|View full text |Cite
|
Sign up to set email alerts
|

Direct impression on agar surface as a diagnostic sampling procedure for candida balanitis

Abstract: Direct impression on CHROMagar candida medium resulted in the highest Candida spp recovery rate. More than 10 colonies yielded by impression culture were statistically associated with candida balanitis. This method shows the ideal profile for sampling the male genital area for yeasts and should be included in the management of balanitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 22 publications
3
13
1
Order By: Relevance
“…We found a point prevalence of candida balanitis of 18%. Previous studies 2–4 reported that 30–35% of the patients with balanitis suffer from candida balanitis; our figure of 45.5% probably results from the higher sensitivity of the impression culture sampling method compared with the swabbing method 18 . Interestingly, the prevalence of candida colonization was 26.2% in this study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found a point prevalence of candida balanitis of 18%. Previous studies 2–4 reported that 30–35% of the patients with balanitis suffer from candida balanitis; our figure of 45.5% probably results from the higher sensitivity of the impression culture sampling method compared with the swabbing method 18 . Interestingly, the prevalence of candida colonization was 26.2% in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Semiquantitative culture methods aimed to establish a meaningful relationship between the amount of yeasts recovered and the likelihood of having typical symptoms and signs of genital candidosis 21,30 . A previous study concluded that there was a significant risk to suffer from candida balanitis whenever the number of the Candida colonies recovered by direct impression was higher than ten 18 . We confirmed this finding, definitely supporting a cut‐off value of 10 candida colonies to develop candida infection.…”
Section: Discussionmentioning
confidence: 99%
“…Yield of yeast from culture is influenced by method of sampling, with the highest recovery rate achieved following direct impression on agar, compared with swabbing with a sterile cotton-tipped swab followed by inoculation on agar. 127 As with VVC, a positive culture result does not differentiate colonization from true infection. 127 Ulcers, if present, should also be cultured for yeast as well as herpes simplex virus, a sample should also evaluated by dark-ground Postgraduate Medicine Downloaded from informahealthcare.com by University of Otago on 07/26/15…”
Section: Diagnosismentioning
confidence: 97%
“…127 As with VVC, a positive culture result does not differentiate colonization from true infection. 127 Ulcers, if present, should also be cultured for yeast as well as herpes simplex virus, a sample should also evaluated by dark-ground Postgraduate Medicine Downloaded from informahealthcare.com by University of Otago on 07/26/15…”
Section: Diagnosismentioning
confidence: 97%
“…In an event-specific study of condom use, Crosby et al 2 report that one important reason it matters is that men are more likely to remove a condom that ‘doesn't fit,’ with implications for STI and HIV transmission (see page ) . Lisboa et al 3 report that the best way to confirm a diagnosis of candidal balanitis is by direct impression on agar (see page ) .…”
mentioning
confidence: 99%